Examination of the partial discharge behaviour within a spherical cavity in insulation paper of transformer - Roslan, Muhammad Hakirin; Azis, Norhafiz; Ab Kadir, Mohd Zainal Abidin; Jasni, Jasronita; Mohd Yousof, Mohd Fairouz (Universiti Putra Malaysia, 2023)
This paper investigates the behaviour of partial discharge (PD) in transformer insulation paper based on the Finite Element Method (FEM). The three-dimensional (3D) FEM model consists of conductor and insulation paper, representing part of a transformer’s high voltage winding. The conductor’s width, height, and length used in this study were 2.4 mm, 11.5 mm, and 16 mm. An insulation paper thickness of 1 mm was modelled around the conductor. An internal cavity with a diameter of 0.5 mm cavity was introduced within the insulation paper. This study introduced two locations of the spherical cavities at the centre and left corner of the insulation paper: Location 1 (L1) and Location 2 (L2). An AC voltage of 33 kV, 50 Hz, was applied to the conductor while the bottom of the insulation paper was grounded. The model was used to study the electric field distribution within the insulation paper and its effect on PD current and charge magnitude. The influence of cavity location on the charge magnitude was also examined. It is found that the electric field distribution is influenced by the conductor configuration as well as the location of the cavity. The electric field in the cavity is the highest at L1 compared to L2. The first PD occurs faster for the cavity with a high electric field. Due to the PD occurrence at the same inception field, the real PD current and charge magnitude is similar at different locations. The apparent PD current and charge magnitude induced at the ground electrode is slightly higher at L1 than at L2.